Alkali-activated slag autoclaved aerated concrete pore structure quality control method
Patent Information
- Application Number
- CN202611487570.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明的目的是提供一种基于多尺度孔结构反馈的碱激发高炉矿渣免蒸压加气混凝土制备调控方法,用以克服现有免蒸压加气混凝土主要依赖发气剂掺量控制干密度、难以同步控制孔径分布、孔隙连通性、吸水性能和导热性能的问题
(1)规则化反馈,避免盲目试错:本发明将孔结构检测结果与参数调整方向、幅度之间的对应关系固化为明确规则,操作人员无需具备丰富经验即可执行标准化调整,克服了现有技术依赖经验性调试的缺陷。
Smart Images

Figure CN122975822A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials, and in particular to a method for controlling the quality of the pore structure of alkali-activated slag non-autoclaved aerated concrete. Background Technology
[0002] Autoclaved aerated concrete (AAC) without autoclaving has broad application prospects in prefabricated enclosures, energy-saving wall materials, and low-carbon building materials due to its lightweight, heat-insulating, and energy-saving characteristics. Compared with traditional autoclaved aerated concrete, the non-autoclaved system eliminates the high-temperature and high-pressure curing process, significantly reducing energy consumption and production costs. Furthermore, using industrial solid waste such as blast furnace slag as precursors to construct the alkali-activated system not only reduces cement clinker usage but also improves the resource utilization level of solid waste. Therefore, alkali-activated slag AAC is considered a new type of building material with both low-carbon properties and engineering application potential. However, most existing AAC technologies still focus on controlling gas generation, i.e., reducing material dry density and increasing porosity by increasing the amount of gas-generating agents such as aluminum powder. While this approach can achieve lower density, it also causes problems such as excessively rapid bubble formation, unstable floating process, and mutual compression and merging of bubbles, ultimately leading to a large number of coarse pores, interconnected pores, and poor-quality pores.
[0003] More importantly, existing technologies for pore structure control generally employ offline experimental design methods (such as orthogonal experiments or single-factor experiments) for one-time parameter screening: that is, a "optimal formula" is determined through multiple sets of experiments during the R&D phase, and this formula is then consistently used in subsequent production. This method has significant drawbacks: (1) Once the production conditions such as raw material batch, ambient temperature and humidity change, the original optimal formula may become invalid, requiring multiple sets of experiments to be carried out again, which is inefficient. (2) During the screening process, only dry density and compressive strength are usually considered, and there is a lack of multi-scale detection and feedback on pore structure quality (uniformity of pore size distribution, proportion of interconnected pores, pore moisture state, etc.), which leads to large fluctuations in product performance; (3) The parameters cannot be adjusted in real time according to the intermediate test results during the trial production process, which often results in the scrapping of the entire batch of samples.
[0004] Therefore, it is urgent to establish a closed-loop feedback control method for alkali-activated slag non-autoclaved aerated concrete. Through multi-scale detection and clear adjustment rules, the quality of the pore structure can be controlled in real time, overcoming the limitations of existing one-time parameter screening methods. Summary of the Invention
[0005] The purpose of this invention is to provide a method for controlling the preparation of alkali-activated blast furnace slag non-autoclaved aerated concrete based on multi-scale pore structure feedback. This method overcomes the problems of existing non-autoclaved aerated concrete, which mainly rely on the dosage of foaming agent to control dry density and have difficulty simultaneously controlling pore size distribution, pore connectivity, water absorption, and thermal conductivity. Through multi-scale detection and closed-loop feedback adjustment of macroscopic, microscopic, and moisture states, the material forms a pore structure characterized by predominantly uniform closed pores, suppressed interconnected pores, balanced pore size distribution, and a high proportion of gel water with short relaxation time. This achieves a synergistic improvement in strength, water absorption, and thermal conductivity.
[0006] To achieve the above objectives, this invention provides a method for quality control of the porous structure of alkali-activated slag non-autoclaved aerated concrete, comprising the following steps: Step 1, Preparation of matrix slurry: Using blast furnace slag powder as a precursor, alkali activator and borax as regulating components, the water-binder ratio, alkali content, water glass modulus and borax dosage are controlled within a specific range, water is added and stirred evenly to obtain alkali activated matrix slurry; Step 2, Gas generation and molding: Add gas generating agent and foam stabilizer to the matrix slurry obtained in Step 1, control the amount of gas generating agent and the mass ratio of foam stabilizer to gas generating agent within a specific range, mix and pour into the mold, complete gas generation, expansion and preliminary shaping under normal pressure to obtain a hardened molded body; Step 3, Detection and Feedback Control: First, the hardened molded body obtained in Step 2 is subjected to pore structure quality detection, which includes at least macroscopic pore structure detection, microscopic pore size distribution detection, and pore moisture state detection; the results of each detection are compared with the corresponding preset indicators. If any test result does not meet the preset index, at least one process parameter in step 1 and / or step 2 shall be adjusted according to the preset corresponding rules, and steps 1 to 3 shall be repeated until all test results meet the preset index. Step 4, Curing: Curing the hardened molded body that meets all preset indicators to obtain alkali-activated slag autoclaved aerated concrete.
[0007] Preferably, in step 1, the alkali activator is a composite alkali activator of water glass and sodium hydroxide; the adjusting component borax also serves as a coagulation and thickening adjusting component; the water-cement ratio of the matrix slurry is controlled to be 0.33~0.38, the alkali content is 4%~6% of the mass of blast furnace slag powder, the water glass modulus is 1.1~1.3, and the borax content is 3%~5% of the mass of blast furnace slag powder.
[0008] Preferably, the gas-generating agent is aluminum powder, and the dosage is 0.125%~0.225% of the mass of blast furnace slag powder; the foam stabilizer is calcium stearate, and the mass ratio of calcium stearate to aluminum powder is 1.0~1.8; and the aluminum powder is added after being prepared into an aluminum powder suspension by mixing with a portion of the mixing water in advance.
[0009] Preferably, the macroscopic pore structure is detected using image analysis to obtain the number of pores and porosity of the intermediate layer; the microscopic pore size distribution is detected using mercury intrusion porosimetry; and the pore moisture state is detected using low-field nuclear magnetic resonance to determine the T2 relaxation time spectrum.
[0010] Preferably, the method for obtaining the number of intermediate pore layers is as follows: N independent specimens are randomly selected from the hardened molded body obtained in step 2, cured for 28 days, and then naturally air-dried. They are then cut into three layers (upper, middle, and lower) at equal intervals along a direction parallel to the molding surface. At the center of the cut surface on the upper side of each intermediate layer, a pore layer with actual dimensions of 100mm × 100mm and an area of 10 mm is selected. 4 mm 2 The statistical region was determined; the image was calibrated to 50 pixels / mm, and 8-bit grayscale and Otsu global thresholding were performed within a 5000×5000 pixel region. Holes were identified according to the 8-neighbor connectivity rule, and the area retained was not less than 0.010 mm. 2 Independent holes that do not touch the boundary of the statistical region are not split into watersheds for connected holes. The arithmetic mean of the hole counts of the N regions is used as the number of holes in the intermediate layer. The porosity of the intermediate layer is calculated using the arithmetic mean of the two-dimensional pore area fractions of the same N statistical regions.
[0011] Preferably, the preset indicators for macroscopic pore structure detection include: the number of intermediate layer pores is not less than 4700, the porosity of the intermediate layer is 30%~34%, and there is no continuous macropore region formed by the aggregation or connection of macropores with d>2.0mm; the preset indicators for microscopic pore size distribution detection include: no dominant peak in the pore size range greater than 60μm in the mercury intrusion porosimetry incremental pore volume curve, distribution in the three capillary pore size ranges of 0.05~0.5μm, 0.5~10μm, and 10~60μm, and the volume fraction difference between each range does not exceed 15 percentage points; the preset indicators for pore moisture state detection include: relatively enhanced signal peak in the gel water region of 0.01~1ms, no dominant peak in the free water region of 100~1000ms, and the ratio of the signal peak area of the gel water region to the signal peak area of the free water region is greater than 1.5.
[0012] Preferred, preset corresponding rules include: When the macroscopic pore structure does not meet the preset index, adjust the dosage of the gas generating agent; the preset index is not met, including: the porosity of the intermediate layer is higher than 34%, the number of pores in the intermediate layer is less than 4700, or there is a continuous macroporous area formed by the aggregation or connection of macropores with d>2.0mm. When the micropore size distribution does not meet the preset index, adjust the mass ratio of foam stabilizer to gas-generating agent; When the pore moisture state does not meet the preset index, adjust the borax dosage.
[0013] Preferably, the specific rules for adjusting the amount of gas-generating agent are as follows: if macroscopic pore structure testing shows that the porosity of the intermediate layer is higher than 34% or the number of pores is less than 4700, or a continuous macroporous area formed by the aggregation or interconnection of macropores with d>2.0mm appears, then the amount of gas-generating agent is reduced to 0.7~0.9 times the original amount; if the porosity of the intermediate layer is lower than 30%, then the amount of gas-generating agent is increased to 1.1~1.3 times the original amount. The specific rules for adjusting the mass ratio of foam stabilizer to gas-generating agent are as follows: If a dominant peak larger than 60 μm appears in the micropore size distribution detection, or if the volume fraction difference between the three intervals of 0.05~0.5 μm, 0.5~10 μm, and 10~60 μm exceeds 15 percentage points, then the mass ratio should be increased to 1.1~1.2 times the original value; if the volume fraction of any interval among the three capillary pore size intervals of 0.05~0.5 μm, 0.5~10 μm, and 10~60 μm exceeds 60% of the total capillary volume, then the mass ratio should be decreased to 0.8~0.9 times the original value. The specific rules for adjusting the borax dosage are as follows: If a dominant peak is formed in the 100-1000ms free water region during pore moisture state detection, or if the area ratio of the gel water region to the free water region is less than 1.5, then increase the borax dosage to 1.1-1.2 times the original dosage; if the slurry thickens too slowly, leading to stratification, then reduce the borax dosage to 0.8-0.9 times the original dosage. Preferably, in step 3, steps 1 to 3 are repeated no more than 3 times. If the preset index is still not met after 3 adjustments, then the raw material or environmental conditions are determined to be outside the controllable range.
[0014] Preferably, in step 4, the curing process is as follows: cut off the part that protrudes from the mold, cover with film, let stand for 24 hours at a temperature of 20±2℃ and a relative humidity of not less than 95%, then demold, and continue to cure under the same conditions for 28 days.
[0015] Therefore, the method for controlling the quality of the pore structure of alkali-activated slag non-autoclaved aerated concrete of the present invention has the following beneficial effects: (1) Regularized feedback to avoid blind trial and error: This invention solidifies the correspondence between the hole structure detection results and the parameter adjustment direction and magnitude into clear rules. Operators do not need to have rich experience to perform standardized adjustments, which overcomes the defects of existing technologies that rely on experience-based debugging.
[0016] (2) Rapid convergence and improved R&D efficiency: Compared with the existing technology, which requires redesigning multiple sets of orthogonal experiments for parameter screening, the present invention can achieve the quality of hole structure by pre-setting adjustment rules, usually requiring only 1 to 3 rounds of repetition, which greatly reduces the number of trials and waste of raw materials.
[0017] (3) Adapt to production fluctuations and enhance robustness: When raw material batches, environmental temperature and humidity and other conditions change, existing fixed formula methods often fail. However, this invention can quickly restore the pore structure quality of the product and ensure product consistency through real-time detection and regular adjustment.
[0018] (4) Multi-scale integrated control: At the same time, macro porosity, micro pore size distribution and pore moisture state are incorporated into the feedback system, realizing systematic control of pore structure quality, so that the material can obtain higher compressive strength and lower thermal conductivity while maintaining a lower dry density.
[0019] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0020] Figure 1 This is a flowchart of the method for controlling the quality of the pore structure of alkali-activated slag non-autoclaved aerated concrete according to the present invention. Figure 2 The figures show a comparison of the macroscopic pore structures of Embodiments 1 and 2 of the present invention and Comparative Example 1, wherein (a) is a comparison of the pores in the intermediate layer and (b) is a comparison of the number of pores in the intermediate layer. Figure 3 The diagram shows a comparison of the comprehensive performance of Embodiments 1 and 2 of the present invention with Comparative Example 1, where (a) is dry density, (b) is compressive strength, (c) is water absorption rate, and (d) is thermal conductivity. Detailed Implementation
[0021] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.
[0022] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments.
[0023] Please see Figure 1 This invention provides a method for controlling the quality of the pore structure of alkali-activated slag non-autoclaved aerated concrete, comprising the following steps: Step 1: Preparation of matrix slurry: Using blast furnace slag powder as a precursor, and a composite alkali activator of water glass and sodium hydroxide and borax as regulating components, borax also serves as a coagulation and thickening regulating component; the water-cement ratio of the matrix slurry is controlled at 0.33~0.38, the alkali content is 4%~6% of the mass of blast furnace slag powder, the water glass modulus is 1.1~1.3, and the borax content is 3%~5% of the mass of blast furnace slag powder. Water is added and stirred evenly to obtain alkali-activated matrix slurry.
[0024] Step 2, Gas generation and molding: Add aluminum powder as a gas generator and calcium stearate as a foam stabilizer to the matrix slurry obtained in Step 1. The amount of aluminum powder is 0.125% to 0.225% of the mass of blast furnace slag powder; the mass ratio of calcium stearate to aluminum powder is 1.0 to 1.8; and the aluminum powder is pre-mixed with a portion of the mixing water to form an aluminum powder suspension before being added. After mixing, the mixture is poured into a mold, and gas generation, expansion and preliminary molding are completed under normal pressure to obtain a hardened molded body.
[0025] Step 3, Detection and Feedback Control: First, the hardened molded body obtained in Step 2 is subjected to pore structure quality detection. This detection includes at least macroscopic pore structure detection, microscopic pore size distribution detection, and pore moisture state detection.
[0026] Macroscopic pore structure detection employs image analysis. The hardened molded body is cut along the direction parallel to the molding surface to obtain the upper, middle, and lower cut surfaces. Image analysis is performed on the middle layer cut surface to obtain the number of pores and the porosity of the middle layer. Specifically, N independent specimens are randomly selected from the hardened molded body obtained in step 2. After curing for 28 days and then air-drying, the specimens are cut along the direction parallel to the molding surface at points H / 3 and 2H / 3 from the bottom surface, using the height H of the shaped specimen as the base. This results in upper, middle, and lower layers. The upper cut surface of the middle layer is uniformly selected, and a cut surface with actual dimensions of 100mm × 100mm and an area of 10 mm is selected at the center of the upper cut surface of the middle layer. 4 mm 2 The statistical region was defined; the image was calibrated to 0.020 mm / pixel, or 50 pixels / mm. Within a 5000×5000 pixel area, 8-bit grayscale conversion and Otsu global thresholding were performed. Holes were identified according to the 8-neighborhood connectivity rule, retaining an area of not less than 0.010 mm². 2 The number of holes in the intermediate layer is the arithmetic mean of the hole counts in the N regions obtained by dividing the interconnected holes into watersheds and independent holes that do not touch the boundary of the statistical region. The porosity of the intermediate layer is calculated using the arithmetic mean of the two-dimensional pore area fractions of the same N statistical regions.
[0027] The macroscopic aperture distribution is also obtained. The area A of a single hole is converted into the equivalent circle diameter d. Holes with d < 1.0 mm are defined as small holes, holes with 1.0 mm ≤ d ≤ 2.0 mm are defined as medium holes, and holes with d > 2.0 mm are defined as large holes.
[0028] The micropore size distribution was detected using mercury porosimetry to test the pore size distribution of the hardened molded body. The pores were classified according to their size into: gel pores <0.05μm, capillary pores 0.05~60μm, and macropores >60μm.
[0029] The T2 relaxation time spectrum of pore water state was determined by low-field nuclear magnetic resonance (NMR). Specifically, the T2 relaxation time spectrum of pore water in the hardened body after gasification and preliminary hardening was determined by low-field NMR. Based on the T2 relaxation time, the pore water state was divided into a gel water region of 0.01~1 ms, a capillary water region of 1~100 ms, and a free water region of 100~1000 ms.
[0030] Each test result is compared with its corresponding preset index; specifically: The preset indicators for macroscopic pore structure detection include: the number of intermediate layer pores is not less than 4700, the porosity of the intermediate layer is 30%~34%, and there is no continuous large pore area formed by the aggregation or connection of large pores with d>2.0mm.
[0031] The preset indicators for detecting micropore size distribution include: no dominant peak in the pore size range greater than 60 μm in the incremental pore volume curve of mercury porosimetry; distribution in the three capillary pore size ranges of 0.05~0.5 μm, 0.5~10 μm, and 10~60 μm; and the difference in volume fraction of each pore does not exceed 15 percentage points.
[0032] The preset indicators for pore moisture state detection include: relative enhancement of signal peaks in the 0.01~1ms gel water region, no dominant peaks in the 100~1000ms free water region, and a ratio of signal peak area in the gel water region to signal peak area in the free water region greater than 1.5.
[0033] If any test result fails to meet the preset criteria, at least one process parameter in step 1 and / or step 2 will be adjusted according to the preset corresponding rules. The preset corresponding rules include: 1) When the macroscopic pore structure does not meet the preset indicators, namely: the porosity of the intermediate layer is higher than 34%, the number of pores in the intermediate layer is less than 4700, or a continuous macroporous area formed by the aggregation or connection of macropores with d>2.0mm appears; adjust the dosage of the gas generating agent. Specifically: if the macroscopic pore structure test shows that the porosity of the intermediate layer is higher than 34% or the number of pores is less than 4700, reduce the dosage of the gas generating agent to 0.7~0.9 times the original dosage; if the porosity of the intermediate layer is lower than 30%, increase the dosage of the gas generating agent to 1.1~1.3 times the original dosage.
[0034] 2) When the micropore size distribution does not meet the preset index, adjust the mass ratio of foam stabilizer to gas generating agent. Specifically: if a dominant peak larger than 60μm appears in the micropore size distribution detection, or the volume fraction difference between the three intervals of 0.05~0.5μm, 0.5~10μm, and 10~60μm exceeds 15 percentage points, then increase the mass ratio to 1.1~1.2 times the original value; if the volume fraction of one of the three capillary pore size intervals of 0.05~0.5μm, 0.5~10μm, and 10~60μm exceeds 60% of the total capillary volume, then decrease the mass ratio to 0.8~0.9 times the original value.
[0035] 3) When the pore moisture state does not meet the preset index, adjust the borax dosage. Specifically: if the 100~1000ms free water region forms a dominant peak in the pore moisture state detection, or the area ratio of the gel water region to the free water region is less than 1.5, increase the borax dosage to 1.1~1.2 times the original dosage; if the slurry thickens too slowly, resulting in stratification, reduce the borax dosage to 0.8~0.9 times the original dosage.
[0036] Repeat steps 1 to 3 until all test results meet the preset indicators. At the same time, it is necessary to ensure that the number of times steps 1 to 3 are repeated does not exceed 3. If the preset indicators are still not met after 3 adjustments, it is determined that the raw materials or environmental conditions are out of the controllable range, and the raw material batch or environmental conditions need to be replaced or adjusted.
[0037] The aforementioned adjustment rules are the key difference between this invention and existing one-time experimental screening: it solidifies the correspondence between "detection results - parameter adjustment direction - adjustment range" into clear rules, as shown in Table 1, so that operators can make standardized adjustments without relying on experience, and the adjustment process only needs to be repeated 1 to 3 times to converge, which is far superior to the existing methods that require redesigning multiple sets of experiments.
[0038] Step 4, Curing: Curing the hardened molded body that meets all preset indicators, cutting off the part that protrudes from the mold, covering it with a film, and letting it stand for 24 hours at a temperature of 20±2℃ and a relative humidity of not less than 95% before demolding. Continue curing under the same conditions for 28 days to obtain alkali-activated slag autoclaved aerated concrete.
[0039] Table 1: Adjustment Rules
[0040] The above steps will be further explained below with reference to specific embodiments.
[0041] Example 1 This embodiment provides a method for quality control of the porous structure of alkali-activated slag non-autoclaved aerated concrete, including the following steps: 1) Preparation of alkali activator solution: Based on the mass of blast furnace slag powder, control the alkali content to be 5% of the blast furnace slag powder mass, and the water glass modulus to be 1.2. Mix water glass, sodium hydroxide, and part of the mixing water to prepare a composite alkali activator solution, and let it stand for 24 hours to allow the solution composition to stabilize.
[0042] 2) Preparation of matrix slurry: Blast furnace slag powder was weighed as a precursor, and the water-cement ratio was controlled at 0.35. The amount of borax added was 4% of the mass of the blast furnace slag powder. First, the blast furnace slag powder and borax were dry-mixed to make the powder evenly dispersed. Then, the prepared composite alkali activator solution and the remaining mixing water were added, and the mixture was stirred at low speed for 1 minute, and then stirred at high speed for 2 minutes to obtain an alkali-activated blast furnace slag matrix slurry.
[0043] In this step, the role of borax is not only to delay setting, but also to adjust the thickening rate of the matrix slurry so that it matches the subsequent aluminum powder gas generation process, avoiding premature hardening of the slurry that causes bubbles to be fixed before they have fully formed, or insufficient thickening of the slurry that causes bubbles to float, merge and break.
[0044] 3) Preparation of aluminum powder suspension: Aluminum powder was weighed as a chemical gas-generating component, with an aluminum powder content of 0.150% of the blast furnace slag powder mass. The aluminum powder was pre-mixed with 20% of the total mixing water mass to prepare an aluminum powder suspension, thereby improving the uniformity of aluminum powder dispersion in the matrix slurry.
[0045] 4) Addition of foam-stabilizing components and foam-generating molding: Weigh calcium stearate according to a mass ratio of calcium stearate to aluminum powder of 1.4, and add it to the alkali-activated blast furnace slag matrix slurry obtained in step 2). After stirring evenly, add the aluminum powder suspension obtained in step 3) and continue stirring at high speed for 30 seconds. Then, quickly pour the slurry into the mold, with the pouring volume being 1 / 3 to 1 / 2 of the mold volume. Under normal pressure, complete the gas generation, expansion, and preliminary shaping to obtain the hardened molded body after gas generation.
[0046] In this step, the amount of aluminum powder determines the amount of hydrogen generated and the intensity of gas generation. The method of adding the aluminum powder suspension is used to improve the uniformity of gas generation, and the mass ratio of calcium stearate to aluminum powder is used to improve bubble stability. Through the synergistic effect of aluminum powder, calcium stearate, and borax, the processes of aluminum powder gas generation, bubble stability, and slurry thickening and hardening are matched.
[0047] 5) Inspect the pore structure quality of the hardened molded body after gas molding. The inspection includes: (1) Macroscopic pore structure detection based on image analysis: The hardened molded body is cut into three layers (upper, middle and lower) along the direction parallel to the molding surface. The middle layer cutting surface is selected for image acquisition and Image-J analysis to obtain the number of pores and porosity of the middle layer. (2) Micropore size distribution detection based on mercury porosimetry: The pore size distribution of the hardened molded body was measured and the pore size was divided into gel pores less than 0.05 μm, capillary pores of 0.05~60 μm and macropores greater than 60 μm. Among them, the capillary pores were further divided into small pores of 0.05~0.5 μm, medium pores of 0.5~10 μm and macropores of 10~60 μm. (3) Detection of pore water state based on low field nuclear magnetic resonance: The T2 relaxation time spectrum of pore water in the hardened molded body was measured, and the T2 relaxation time was divided into the gel water region of 0.01~1ms, the capillary water region of 1~100ms and the free water region of 100~1000ms.
[0048] Testing revealed that the intermediate layer porosity of the hardened molded body obtained in this embodiment is approximately 32.34% to 32.35%, and the number of intermediate layer pores is 5963, which meets the preset requirements of an intermediate layer porosity of 30% to 34% and a number of intermediate layer pores of not less than 4700.
[0049] The mercury porosimetry test results show that the pore size distribution of the material obtained in this embodiment is relatively uniform, and there is no pore size distribution dominated by the 10~60μm or larger than 60μm pore size range.
[0050] Low-field nuclear magnetic resonance (NMR) test results show that the T2 spectrum of the material obtained in this embodiment has a strong gel water signal with short relaxation time, while the free water signal with long relaxation time does not form a dominant peak, indicating that the pore water state is relatively stable.
[0051] Therefore, the hardened molded body obtained in this embodiment meets the preset pore structure quality requirements and does not require further adjustment of the aluminum powder content, the mass ratio of calcium stearate to aluminum powder, or the borax content.
[0052] 6) Removal, Coating, and Curing: After the slurry has basically completed gas generation, remove the portion protruding above the mold and coat the surface of the specimen. Place the specimen in an environment with a temperature of 20±2℃ and a relative humidity of not less than 95% for 24 hours before demolding. After demolding, continue curing under the same conditions until the specified age.
[0053] Performance tests were conducted on alkali-activated blast furnace slag non-autoclaved aerated concrete cured for 28 days. The results showed that its 28-day dry density was 711.05 kg / m³. 3 It has a compressive strength of 7.81 MPa, a flexural strength of 1.62 MPa, a thermal conductivity of 0.162 W / (m·K), and a water absorption rate of 47.44%.
[0054] This demonstrates that under the conditions of a water-cement ratio of 0.35, an alkali content of 5%, a water glass modulus of 1.2, a borax content of 4%, an aluminum powder content of 0.150%, and a calcium stearate to aluminum powder mass ratio of 1.4, it is possible to obtain alkali-activated blast furnace slag autoclaved aerated concrete with a relatively uniform pore structure, moderate dry density, high compressive strength, and low thermal conductivity.
[0055] Example 2 This embodiment illustrates how to gradually adjust the process parameters according to the feedback control rules of the present invention until all indicators meet the requirements when the pore structure quality test results of the hardened molded body do not meet the preset indicators.
[0056] The specific steps are as follows: S1. Initial parameter settings: This embodiment uses slightly different initial parameters than Example 1, specifically: water-cement ratio 0.36, alkali content 5%, water glass modulus 1.2, borax content 4%, aluminum powder content 0.175%, and calcium stearate to aluminum powder mass ratio 1.3. The aluminum powder content (0.175%) is higher than the 0.150% in Example 1, and the calcium stearate to aluminum powder mass ratio (1.3) is slightly lower than the 1.4 in Example 1, serving as an example to illustrate the possible pore structure quality deviations under this parameter combination and their feedback adjustment process.
[0057] The remaining steps are the same as in Example 1, and the first preparation is performed according to steps 1 to 4.
[0058] S2, First Hole Structure Quality Inspection: The pore structure quality of the hardened molded body obtained in the first preparation was tested, and the results are as follows: (1) Macroscopic pore structure detection: The porosity of the intermediate layer is 36.2% (higher than the preset upper limit of 34%), the number of pores in the intermediate layer is 4460 (less than the preset lower limit of 4700), and image analysis shows that there are continuous large pore areas formed by the aggregation of large pores with d>2.0mm in some local areas. The macroscopic pore structure does not meet the preset indicators.
[0059] (2) Micropore size distribution detection: Mercury porosimetry results showed that the volume fraction of the pore size range greater than 60 μm was 38%, forming a distinct dominant peak; the volume fractions of the three capillary pore size ranges of 0.05~0.5 μm, 0.5~10 μm, and 10~60 μm were 22%, 26%, and 14%, respectively, with the maximum difference (26%-14%=12 percentage points) not exceeding 15 percentage points. However, due to the dominant peak in the greater than 60 μm range, the micropore size distribution did not meet the preset index.
[0060] (3) Detection of pore moisture state: Low-field nuclear magnetic resonance T2 spectrum showed that a distinct dominant peak was formed in the 100~1000ms free water region, and the ratio of the signal peak area in the 0.01~1ms gel water region to the signal peak area in the free water region was 0.8 (less than the preset lower limit of 1.5). The pore moisture state did not meet the preset index.
[0061] In summary, none of the three test results met the preset indicators, and feedback adjustments are needed.
[0062] S3. Adjust parameters according to the control rules: According to the preset correspondence rules of the present invention: (1) The macroscopic pore structure does not meet the requirements (porosity is too high, number of pores is too low, and continuous large pore areas appear) → reduce the aluminum powder content. Reduce the aluminum powder content from 0.175% to 0.85 times the original content, that is, adjust it to 0.149% (about 0.15%).
[0063] (2) The micropore size distribution does not meet the requirements (the dominant peak is formed in the range greater than 60 μm) → increase the mass ratio of calcium stearate to aluminum powder. Increase the mass ratio from 1.3 to 1.15 times the original value, that is, adjust it to 1.495 (about 1.5).
[0064] (3) The pore moisture state does not meet the requirements (free water zone is dominant, and the area ratio is low) → increase the borax content. Increase the borax content from 4% to 1.1 times the original content, that is, adjust it to 4.4%.
[0065] S4. Second preparation and testing: Using the adjusted parameters (aluminum powder content 0.15%, calcium stearate / aluminum powder mass ratio 1.5, borax content 4.4%, other parameters unchanged), steps 1 to 3 were repeated for a second preparation. The pore structure quality of the resulting hardened molded body was then tested again, and the results are as follows: (1) Macroscopic pore structure detection: The porosity of the intermediate layer is 33.1% (within the range of 30%~34%), and the number of pores in the intermediate layer is 5180 (greater than 4700). Image analysis did not find any continuous large pore areas formed by the aggregation or connection of large pores with d>2.0mm. The macroscopic pore structure meets the preset indicators.
[0066] (2) Micropore size distribution detection: The mercury porosimetry test results showed that the volume fraction of the pore size range greater than 60 μm dropped to 16%, and no dominant peak was formed; the volume fractions of the three capillary pore size ranges of 0.05~0.5 μm, 0.5~10 μm, and 10~60 μm were 28%, 32%, and 24%, respectively, with a difference of 8 percentage points, which met the preset index.
[0067] (3) Detection of pore moisture state: The low-field nuclear magnetic resonance T2 spectrum showed that no dominant peak was formed in the free water region from 100 to 1000 ms, and the ratio of the signal peak area in the gel water region to the signal peak area in the free water region from 0.01 to 1 ms was 1.8 (greater than 1.5). The pore moisture state met the preset index.
[0068] S5. Confirmation of control results and maintenance: After one round of feedback and adjustments, all hole structure quality inspection indicators met the preset requirements, and no further adjustments were needed. The hardened molded body that met the indicators was cured according to step 4: the part protruding from the mold was cut off, a film was applied, and it was left to stand for 24 hours at a temperature of 20±2℃ and a relative humidity of not less than 95% before demolding. It was then cured under the same conditions for 28 days.
[0069] Performance tests were conducted on alkali-activated slag autoclaved aerated concrete cured for 28 days. The results showed that the dry density at 28 days was 695 kg / m³. 3 The compressive strength is 7.3 MPa, the flexural strength is 1.55 MPa, and the thermal conductivity is 0.158 W / (m²). The water absorption rate is 51.2%. All performance indicators meet the requirements of grade B06 in JC / T 2660-2022 "Autoclaved Aerated Concrete Blocks".
[0070] This embodiment demonstrates that when the initial parameters deviate from the preferred range (such as the aluminum powder content being too high and the calcium stearate / aluminum powder mass ratio being too low in this embodiment), resulting in substandard pore structure quality, the parameters can be adjusted through the preset feedback control rules of this invention. Only one round of repetition is needed to restore the pore structure quality to a state that meets the requirements, verifying the effectiveness and rapid convergence of the control method of this invention.
[0071] Comparative Example 1 This comparative example uses a higher aluminum powder content (0.225%), while other parameters are exactly the same as in Example 1 (water-cement ratio 0.35, alkali content 5%, water glass modulus 1.2, borax content 4%, calcium stearate to aluminum powder mass ratio 1.4, and aluminum powder suspension preparation method is the same). This is to simulate the situation where feedback control based on pore structure is not implemented, and the sole aim is to reduce dry density.
[0072] The results of its pore structure detection are compared with those of Examples 1 and 2. Figure 2 As shown, specifically: The porosity of the intermediate layer was 40.77%, exceeding the preset upper limit of 34%; the number of pores in the intermediate layer was 5437, exceeding 4700, which numerically met the lower limit for pore number. Mercury intrusion porosimetry results showed that the volume fractions of the five pore size ranges (less than 0.05 μm, 0.05–0.5 μm, 0.5–10 μm, 10–60 μm, and greater than 60 μm) were 2.73%, 18.30%, 53.85%, 15.97%, and 9.15%, respectively; the maximum difference among the three capillary pore size ranges was 37.88 percentage points (53.85%–15.97%), exceeding 15 percentage points. Pore moisture state detection showed that the free water region formed the dominant peak, with a gel water / free water area ratio of 0.7. In other words, all pore structure quality indicators of the comparative example did not meet the preset requirements.
[0073] Its performance was tested and compared with that of Examples 1 and 2. The specific results are shown in Table 2 and... Figure 3 As shown.
[0074] Table 2: Performance Comparison
[0075] The above comparison shows that although the dry density and thermal conductivity of the comparative example decreased slightly, the compressive strength was significantly reduced, and the water absorption rate was too high, making the product unable to meet actual use requirements. According to the control rules of this invention, when "intermediate layer porosity > 34% or number of pores < 4700", the aluminum powder content should be reduced to 0.7 to 0.9 times the original content. Comparative example 1 did not implement this feedback control, resulting in pore structure deterioration, which in turn verifies the effectiveness of the control rules of this invention.
[0076] The method provided by this invention can be applied to the industrial production of lightweight building materials such as aerated concrete blocks and panels, and is particularly suitable for scenarios involving the preparation of autoclaved aerated concrete using industrial solid waste such as blast furnace slag. By implementing this invention, process parameters can be quickly adjusted based on pore structure detection results, significantly improving product quality stability and reducing scrap rates, resulting in significant economic and social benefits. This method requires less equipment investment and consumes less energy, aligning with the national direction of green building materials and circular economy development.
[0077] Therefore, this invention provides a method for controlling the pore structure quality of alkali-activated slag non-autoclaved aerated concrete. Instead of using porosity as the sole control object, it focuses on pore structure quality as the core control objective, fundamentally resolving the contradiction between "lightweighting leading to strength reduction" and "porousness not necessarily improving thermal performance." Furthermore, through the synergistic control of the gas-generating system and the bubble-stabilizing system, it suppresses bubble merging, pore wall rupture, and the formation of interconnected pores, enabling the material to form a multi-scale pore structure dominated by uniform closed pores, thereby improving the continuity and load-bearing efficiency of the solid skeleton.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for controlling the quality of the pore structure of alkali-activated slag non-autoclaved aerated concrete, characterized in that, Includes the following steps: Step 1, Preparation of matrix slurry: Using blast furnace slag powder as a precursor, and alkali activator and borax as regulating components, water is added and stirred evenly to obtain alkali activated matrix slurry; Step 2, Gas generation and molding: Add gas generation agent and foam stabilizer to the matrix slurry obtained in Step 1, mix and pour into the mold, complete gas generation, expansion and preliminary shaping under normal pressure to obtain a hardened molded body; Step 3, Detection and Feedback Control: First, the hardened molded body obtained in Step 2 is subjected to pore structure quality detection, which includes at least macroscopic pore structure detection, microscopic pore size distribution detection, and pore moisture state detection; the results of each detection are compared with the corresponding preset indicators. If any test result does not meet the preset index, at least one process parameter in step 1 and / or step 2 shall be adjusted according to the preset corresponding rules, and steps 1 to 3 shall be repeated until all test results meet the preset index. Step 4, Curing: Curing the hardened molded body that meets all preset indicators to obtain alkali-activated slag autoclaved aerated concrete.
2. The method for quality control of the porous structure of alkali-activated slag non-autoclaved aerated concrete according to claim 1, characterized in that: In step 1, the alkali activator is a composite alkali activator of water glass and sodium hydroxide; the adjusting component borax is used as a coagulation and thickening adjusting component; the water-cement ratio of the matrix slurry is controlled to be 0.33~0.38, the alkali content is 4%~6% of the mass of blast furnace slag powder, the water glass modulus is 1.1~1.3, and the borax content is 3%~5% of the mass of blast furnace slag powder.
3. The method for quality control of the porous structure of alkali-activated slag non-autoclaved aerated concrete according to claim 2, characterized in that: The gas-generating agent is aluminum powder, with an addition amount of 0.125%~0.225% of the mass of blast furnace slag powder; the foam stabilizer is calcium stearate, with a mass ratio of calcium stearate to aluminum powder of 1.0~1.8; and the aluminum powder is added after being pre-mixed with a portion of the mixing water to form an aluminum powder suspension.
4. The method for quality control of the porous structure of alkali-activated slag non-autoclaved aerated concrete according to claim 3, characterized in that: Macroscopic pore structure detection was performed using image analysis to obtain the number of intermediate layer pores and the porosity of the intermediate layer; microscopic pore size distribution was detected using mercury intrusion porosimetry; and pore moisture state was detected by measuring the T2 relaxation time spectrum using low-field nuclear magnetic resonance.
5. The method for quality control of the porous structure of alkali-activated slag non-autoclaved aerated concrete according to claim 4, characterized in that, The method for obtaining the number of intermediate pore layers is as follows: N independent specimens are randomly selected from the hardened molded body obtained in step 2. After curing for 28 days, they are naturally air-dried and then equidistantly cut into upper, middle, and lower layers along a direction parallel to the molding surface. At the center of the cut surface on the upper side of each intermediate layer, a pore size of 100mm × 100mm and an area of 10 mm are selected. 4 mm 2 The statistical region was determined; the image was calibrated to 50 pixels / mm, and 8-bit grayscale and Otsu global thresholding were performed within a 5000×5000 pixel region. Holes were identified according to the 8-neighbor connectivity rule, and the area retained was not less than 0.010 mm. 2 Independent holes that do not touch the boundary of the statistical region are not split into watersheds for connected holes. The arithmetic mean of the hole counts of the N regions is used as the number of holes in the intermediate layer. The porosity of the intermediate layer is calculated using the arithmetic mean of the two-dimensional pore area fractions of the same N statistical regions.
6. The method for quality control of the porous structure of alkali-activated slag non-autoclaved aerated concrete according to claim 5, characterized in that, The preset indicators for macroscopic pore structure detection include: the number of pores in the intermediate layer is not less than 4700, the porosity of the intermediate layer is 30%~34%, and there is no continuous large pore area formed by the aggregation or connection of large pores with d>2.0mm. The preset indicators for the detection of micropore size distribution include: no dominant peak in the pore size range greater than 60 μm in the incremental pore volume curve of mercury porosimetry; distribution in the three capillary pore size ranges of 0.05~0.5 μm, 0.5~10 μm, and 10~60 μm; and the difference in volume fraction between each range does not exceed 15 percentage points. The preset indicators for pore moisture state detection include: relative enhancement of signal peaks in the 0.01~1ms gel water region, no dominant peaks in the 100~1000ms free water region, and a ratio of signal peak area in the gel water region to signal peak area in the free water region greater than 1.
5.
7. The method for quality control of the porous structure of alkali-activated slag non-autoclaved aerated concrete according to claim 6, characterized in that, The preset corresponding rules include: When the macroscopic pore structure does not meet the preset index, adjust the dosage of the gas generating agent; When the micropore size distribution does not meet the preset index, adjust the mass ratio of foam stabilizer to gas-generating agent; When the pore moisture state does not meet the preset index, adjust the borax dosage.
8. The method for quality control of the porous structure of alkali-activated slag non-autoclaved aerated concrete according to claim 7, characterized in that: The specific rules for adjusting the amount of gas-generating agent are as follows: If macroscopic pore structure testing shows that the porosity of the intermediate layer is higher than 34% or the number of pores is less than 4700, or if a continuous macroporous area is formed by the aggregation or interconnection of macropores with d>2.0mm, then reduce the amount of gas-generating agent to 0.7~0.9 times the original amount; if the porosity of the intermediate layer is lower than 30%, then increase the amount of gas-generating agent to 1.1~1.3 times the original amount. The specific rules for adjusting the mass ratio of foam stabilizer to gas-generating agent are as follows: If a dominant peak larger than 60 μm appears in the micropore size distribution detection, or if the volume fraction difference between the three intervals of 0.05~0.5 μm, 0.5~10 μm, and 10~60 μm exceeds 15 percentage points, then the mass ratio should be increased to 1.1~1.2 times the original value; if the volume fraction of any interval among the three capillary pore size intervals of 0.05~0.5 μm, 0.5~10 μm, and 10~60 μm exceeds 60% of the total capillary volume, then the mass ratio should be decreased to 0.8~0.9 times the original value. The specific rules for adjusting the borax dosage are as follows: if a dominant peak is formed in the 100~1000ms free water region during pore moisture state detection, or if the area ratio of the gel water region to the free water region is less than 1.5, then increase the borax dosage to 1.1~1.2 times the original dosage; if the slurry thickens too slowly, resulting in stratification, then reduce the borax dosage to 0.8~0.9 times the original dosage.
9. The method for quality control of the porous structure of alkali-activated slag non-autoclaved aerated concrete according to claim 8, characterized in that: In step 3, the number of times steps 1 to 3 are repeated shall not exceed 3. If the preset index is still not met after 3 adjustments, it is determined that the raw materials or environmental conditions are out of control range.
10. The method for quality control of the porous structure of alkali-activated slag non-autoclaved aerated concrete according to claim 9, characterized in that: In step 4, the curing process is as follows: cut off the part that protrudes above the mold, cover with film, let stand for 24 hours at a temperature of 20±2℃ and a relative humidity of not less than 95%, then demold and continue curing under the same conditions for 28 days.